The exploitation of natural resources in Area C of the West Bank as indicator of annexation - Sánchez, María Fernanda Cáceres (Africana Studia, 2022)
This paper will review whether Israel’s exploitation of Palestinian natural resources, specifically in Area C of the West Bank, serves as an indicator that the occupation has crossed the line into de facto annexation of this area. For this purpose, it will examine how the exploitation is conducted in respect of various natural resources. It will subsequently analyse the concept of occupation, particularly the law of occupation in relation to the exploitation of natural resources, based on Article 55 of the Hague Regulations, and the principle of Permanent Sovereignty of Natural Resources. It will then examine the concept of annexation, and the requirements for a situation to constitute annexation, being the intent to annex the distinctive element. From the analysis, the conclusion will be drawn that Israel exploits the natural resources in Area C of the West Bank not as occupier, but as a sovereign power, with a clear intention to annex the territory, and consequently, this exploitation serves as an indicator to prove that the occupation has crossed the line into de facto annexation. Keywords: Israel, West Bank, natural resources, annexation.